Intersexualidade e direito ao próprio corpo: garantia à integridade corporal da criança intersexual e direito à autodeterminação na adolescência - Erika Aparecida Pretes (2019)
Recent discussions about the possibility of medical and biotechnological intervention for sexual readjustment purposes in intersexual people under the age of 18 have raised questions about the legitimacy of legal guardians and health professional teams for initiating such procedures. In our legal system, persons under 18 years of age have been deemed incapable - relative or absolutely - of providing free and informed consent for any medical interventions, be they small and simple or invasive and painful procedures, as is the case of readjustment surgeries. In the name of "biological and social urgency", children and adolescents diagnosed as intersexual are submitted to various medical and surgical procedures that ensure from early childhood the correction of any "anatomical sexual atypicality". In medical terms, it is believed that such conformity of the phenotype to "gender identity" would guarantee the adequate psychosocial and sexual well-being of these subjects. The surgical and hormonal procedures for sexual readjustment performed in intersex children and adolescents are based on normalizing discourses and practices that seek the adequacy of bodies considered abnormal to a gender pattern established in the heteronormative matrix. Such early biomedical interventions deny the intersexual subject the right to self-determination and the right to one's own body. The parameters adopted in Brazil for the management and medical treatment of intersex persons under 18 years of age hinders the right to their own bodies and selfdetermination. It puts at risk personal integrity (physical and psychological) and the free development of personality by allowing the decision on sexual readjustment to be made by a person other than the one who will undergo the intervention in their own body. We question here the legitimacy for the proceeding of an early medical intervention that denies participation to that subject who will have to endure in their own body all the surgical procedures, the effects of the treatment and the subjective, psychological, social and political repercussions of the choice about belonging to a sex / gender in a sexist and heteronomative society such as ours.